2020
DOI: 10.3390/cancers12123620
|View full text |Cite
|
Sign up to set email alerts
|

CNS Invasion in Meningioma—How the Intraoperative Assessment Can Improve the Prognostic Evaluation of Tumor Recurrence

Abstract: The detection of the infiltrative growth of meningiomas into CNS tissue has been integrated into the WHO classification as a stand-alone marker for atypical meningioma. However, its prognostic impact has been questioned. Infiltrative growth can also be detected intraoperatively. The prognostic impact of the intraoperative detection of the central nervous system tissue invasion of meningiomas was analyzed and compared to the histopathological assessment. The clinical data of 1517 cases with follow-up data regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…The fundamental cause for the absence of CNS tissue is that neurosurgeons tend to keep the arachnoid membrane intact wherever possible to prevent neurological injury. Another possible explanation is nonstandardized intraoperative tumor sampling ( 37 ). Several operation-related variables, including partial resection and the use of a cavitron ultrasonic surgical aspirator (CUSA), appear to be relevant to the reduced ease of access to CNS tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fundamental cause for the absence of CNS tissue is that neurosurgeons tend to keep the arachnoid membrane intact wherever possible to prevent neurological injury. Another possible explanation is nonstandardized intraoperative tumor sampling ( 37 ). Several operation-related variables, including partial resection and the use of a cavitron ultrasonic surgical aspirator (CUSA), appear to be relevant to the reduced ease of access to CNS tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To remedy this shortcoming, two recent studies ( 37 , 39 ) sought to ascertain the advantages of a hybrid strategy that contained knowledge from both operative and pathological observations. Their early findings showed that the combined method had the ability to transcend the shortcomings of sole neuropathological evaluation and may be of considerable therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the long-established histopathological assessment according to the WHO classification of central nervous system tumors [4], the detection of infiltrative meningioma growth into brain parenchyma has been added as a stand-alone criterion for atypia [4]. However, its prognostic significance has since been questioned based on contradictory results of retrospective analyses [6][7][8][9] and its role for tumor grading in the WHO classification is frequently discussed [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last 2016 WHO classification, histopathological evidence of brain infiltration has been integrated as a marker for atypical meningioma, with an impact on prognosis [3]. Even so, some authors remark that histopathological assessment could be biased, as invasive margins may not be surgically resected, therefore impeding histopathological detection [4]. It is also well known that brain invasion or adhesion complicates surgical dissection and increases the risk of stroke, haemorrhage, and other injuries [5].…”
mentioning
confidence: 99%